Affective Learning in Physical Education: A Systematic Review - Teraoka, Eishin; Ferreira, Heidi Jancer [UNESP]; Kirk, David; Bardid, Farid (Human Kinetics Publ Inc, 2021)
Purpose: The purpose of this study was to carry out a systematic review of intervention programs that have addressed affective learning outcomes within physical education and to explore pedagogical practices in alignment with teaching, lesson content, and learning outcomes. Method: The literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Included were 26 peer-reviewed pedagogical studies of physical education programs that addressed affective outcomes and reported fidelity of implementation. Results and Discussion: Affective outcomes were grouped into four themes: motivation, emotional responses, self-concept, and resilience. The findings showed that offering choice, encouraging peer feedback, asking deductive questions, focusing on personal improvement, and differentiating are effective teaching strategies that were widely used to support affective learning in children and adolescents. This review highlights the importance of fidelity of implementation to understand how intervention programs are delivered.
Keywords: fidelity of implementation; intervention programs; motivation; pedagogy; social and emotional learning